2020
DOI: 10.1177/0960327120947451
|View full text |Cite
|
Sign up to set email alerts
|

Short term chronic toxicity of tributyltin on the testes of adult albino rats and the possible protective role of omega-3

Abstract: The declining rate of male fertility is a growing concern. Tributyltin (TBT) is a well-known endocrine disruptor (ED), that induces imposex in female gastropods and is widely used in various industrial applications. The aim of this study was to evaluate the toxic effects of TBT on the testes of adult albino rats and the possible role of omega-3. Forty two adult male albino rats were divided into five groups; control group (Group I) and four experimental groups: omega-3 treated group, TBT treated group, TBT &am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“… 31 Therefore, depleting endogenous germ cells via a single injection of busulfan has become the most commonly used technique for establishing animal models of disrupted spermatogenesis. 32 Many in vivo studies have suggested that omega‐3 can alleviate testicular damage caused by environmental pollutants or metabolic disorders by alleviating oxidative stress, 33 reducing apoptosis, 34 repairing the blood‐testis barrier, 35 and protecting against DNA damage. 36 Notably, our results showed that omega‐3 could restore spermatogenesis by increasing the thickness of the spermatogenic tubule epithelium, alleviating spermatogenic cell apoptosis, and increasing the number of sperm in the caudal epididymis (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“… 31 Therefore, depleting endogenous germ cells via a single injection of busulfan has become the most commonly used technique for establishing animal models of disrupted spermatogenesis. 32 Many in vivo studies have suggested that omega‐3 can alleviate testicular damage caused by environmental pollutants or metabolic disorders by alleviating oxidative stress, 33 reducing apoptosis, 34 repairing the blood‐testis barrier, 35 and protecting against DNA damage. 36 Notably, our results showed that omega‐3 could restore spermatogenesis by increasing the thickness of the spermatogenic tubule epithelium, alleviating spermatogenic cell apoptosis, and increasing the number of sperm in the caudal epididymis (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The three major O3FAs are docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA) and alpha-linolenic acid (ALA). These three are required for a variety of functions, including growth, reproduction, vision, and the development of the brain 11 . While the data reporting the beneficial effect of O3FA on male sexual performance is lacking, it has been shown to have vasodilatory effect in different vascular beds 12 , and by extension, could cause vasodilation of smooth muscle of corpora cavernosa which can improve male sexual function via NO/cGMP signaling.…”
Section: Introductionmentioning
confidence: 99%